Austrian nitrogen budget following UNECE guidance - Ika Djukic; Carina Broneder; Thomas Dirnböck; Oliver Gabriel; Helga Lindinger; Harald Loishandl-Weisz; Simone Mayer; Christian Nagl; Stephan Poupa; Helmut Rechberger; Philip Sander; Bettina Schwarzl; et al. (Environmental Research Letters)
Human activity over the past century has greatly disrupted the natural nitrogen (N) balance, harming health and the environment. Sustainable nitrogen management requires cross-sectoral governance, but studies tracking nitrogen flows across sectors are limited. This study assesses cross-sectoral sources, flows, and sinks of reactive nitrogen (Nr) in Austria, identifying direct N _r inputs and emitting sectors. Using the ‘UNECE-Guidance Document on National Nitrogen Budgets’ and material flow analysis, we quantified Austria’s national nitrogen budget for 2015–2019. Results show the main nitrogen inflows and outflows from imports and exports in the consumer goods and chemical industries. Energy imports also contribute significantly. Some nitrogen is temporarily stored (e.g. in products) or transferred between sectors. However, not all of this N-loss is of direct environmental concern. Annually, 389 kt N _r are lost directly to the environment and causing significant environmental and economic consequences. Direct N _r inputs primarily originate from agriculture (39.3%) and energy/transport (20.7%), with around 30% from cross-border fluxes via water (13.9%) and air (16.6%). The remaining 10% stem from settlements, waste management, and industry. This study highlights the complexity of nitrogen sources and sinks in Austria and underscores the need for improvements towards reduced uncertainties in future research, including higher-resolution spatial data to account for regional variability.